Funding Pattern of Small Business Enterprises in India: An Empirical Study: Exploring the Funding Pattern of Small Business Enterprises in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A regular and continuous flow of funds is a very essential component of a successful business. The funds are essential part for the organization to meet various required outflows such as, funds are required for sales promotion, advertising, and other general overhead expenses salaries, wages and conveyance are to pay raw materials are to purchase and equipment need to be purchased and serviced reserves are needed to be made till the customers make their payment. Different short term and long-term sources of financing is truly the blood circulation in the veins of any business firm. Now the important question come up as to how do a business obtain funds from different sources. There are a number of different avenues of financing. A business may fulfill its financing needs keeping in mind the nature of requirements and nature and cost of the concerned source of financing. Due to many policies framed by the government new entrepreneurs are coming up with new business ideas. The culture of startups is developing in India. The young generation prefers to start their own business rather than joining existing companies. A regular and continuous flow of funds is a very essential component of a successful business. Funds are an essential and flowing part of a successful business. It is particularly needed for various operating and non-operating activities of the business such as, paying remuneration to staff, purchasing raw material, paying for marketing, for making reserves until the customers pay their credit. Different short term long-term sources of financing is truly the blood circulation in the veins of any business firm. Now the important question come up as to how do a business obtain funds from different sources. Only a small portion of SMEs thus far have successfully received this funding and this big gap poses a question mark and triggers the need to conduct a study. In the study the responses are collected from 310 entrepreneurs who are in the process of expanding their new startups.